2004
DOI: 10.1200/jco.2004.09.127
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Functional Outcomes in the 5 Years After Diagnosis of Localized Prostate Cancer

Abstract: This long-term cohort study found that, among prostatectomy patients, African-Americans had better recovery of sexual and urinary function at 60 months after diagnosis that was likely to be of mild clinical significance, despite reporting more problems with sexual function than non-Hispanic whites. More study is necessary to understand reasons for these differences. In contrast, no racial/ethnic differences in recovery from radiotherapy were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 29 publications
2
70
0
Order By: Relevance
“…African-American men reported greater rates of loss of desire following treatment, but they had more positive attitudes about help seeking. A 5-year prospective study reported by Johnson et al 47 surveyed 1475 nonHispanic white, 321 African-American and 279 Hispanic prostate cancer patients on their urinary, bowel and sexual functioning. At 60-month followup, radiation patients of all ethnic groups reported fairly similar outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…African-American men reported greater rates of loss of desire following treatment, but they had more positive attitudes about help seeking. A 5-year prospective study reported by Johnson et al 47 surveyed 1475 nonHispanic white, 321 African-American and 279 Hispanic prostate cancer patients on their urinary, bowel and sexual functioning. At 60-month followup, radiation patients of all ethnic groups reported fairly similar outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Previously, we detailed HRQOL recovery in Japanese men with localized prostate cancer followed for 2 years after RP. 6 In the current analysis we assessed temporal changes in HRQOL up to 5 years following RP using validated questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,20,21 Despite the importance of this work, there has been little effort to examine if a better understanding of the consequences that commonly result from managing early-stage prostate cancer translate into better recognition and management of functional and quality-of-life deficits or to improvements in the survivorship experience. A major barrier to achieving this goal has been the failure to incorporate patient-reported QOL widely into clinical practice.…”
Section: Discussionmentioning
confidence: 99%